Early Implantation as a Main Predictor of Response to Vagus Nerve Stimulation in Childhood-Onset Refractory Epilepsy. (April 2021) - Russo, Angelo; Hyslop, Ann; Gentile, Valentina; Chiarello, Daniela; Messana, Tullio; Miller, Ian; Zucchelli, Mino; Lima, Mario; Ragheb, John; Pini, Antonella; Cordelli, Duccio Maria; Resnick, Trevor; et al.
Objective: We describe a multicenter experience with vagus nerve stimulator implantation in pediatric patients with drug-resistant epilepsy. Our goal was to assess vagus nerve stimulation efficacy and identify potential predictors of favorable outcome. Methods: This is a retrospective study. Inclusion criteria: ≤18 years at time of vagus nerve stimulator implantation, at least 1 year of follow-up. All patients were previously found to be unsuitable for an excisional procedure. Favorable clinical outcome and effective vagus nerve stimulation therapy were defined as seizure reduction >50%. Outcome data were reviewed at 1, 2, 3, and 5 years after vagus nerve stimulator implantation. Fisher exact test and multiple logistic regression analysis were employed. Results: Eighty-nine patients met inclusion criteria. Responder rate (seizure frequency reduction >50%) at 1-year follow-up was 25.8% (4.5% seizure-free). At last follow-up, 31.5% had a favorable outcome and 5.2% were seizure free. The only factor significantly predicting favorable outcome was time to vagus nerve stimulator implantation, with the best outcome achieved when vagus nerve stimulator implantation was performed within 3 years of seizure onset. Implantation between 3 and 5 years after epilepsy onset correlated with better long-term seizure freedom (13.3% at T5). Overall, 65.2% of patients evidenced improved quality of life at last follow-up. However, 12.4% had adverse events, but most were mild and disappeared after 3-4 months. Conclusions: Early vagus nerve stimulator implantation within 5 years of seizure onset was the only predictor of favorable clinical outcome in pediatric patients. Improved quality of life and a low incidence of significant adverse events were observed.